Protesi di rivestimento di anca - Calanna, F.; Gala, L. (Lo Scalpello - Journal, 2019)
HIP RESURFACING ARTHROPLASTY Hip resurfacing arthroplasty is a concept of hip replacement surgery developed specifically for young and active patients. Femoral bone stock preservation and restoring of normal anatomy of the hip joint allow for better functioning, with increased frequency and duration of sporting activities. Patient-related factors leading to worse outcomes have also been identified. Moreover, concerns about metal-on-metal bearings with adverse reaction to metal debris have led to a recent drop-off in this kind of procedure. The purpose of this study was to evaluate current trends about hip resurfacing and comparing it to standard hip replacement arthroplasty. Hip resurfacing still represents a viable option with a correct indication, in the right hands and using a device with a long track record.